2019
DOI: 10.3847/1538-4357/ab0e01
|View full text |Cite
|
Sign up to set email alerts
|

The Sequence of Coronene Hydrogenation Revealed by Gas-phase IR Spectroscopy

Abstract: Gas-phase coronene cations (C H 24 12 + ) can be sequentially hydrogenated with up to 24 additional H atoms, inducing a gradual transition from a planar, aromatic molecule toward a corrugated, aliphatic species. The mass spectra of hydrogenated coronene cations C H n 24 12 H + + [ ] show that molecules with odd numbers of additional hydrogen atoms (n H ) are dominant, with particularly high relative intensity for "magic numbers" n H =5, 11, and 17, for which hydrogen atoms have the highest binding energies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…The observations also show that the quasi-equilibrium is shifted towards HNCO because of a small barrier for the reaction H + HNCO → H 2 NCO. Similar dual-cycle mechanism might link also other unsaturated/saturated pairs of interstellar molecules; e.g., recent studies indicated the existence of similar cycles among CO, H 2 CO and CH 3 OH (Chuang et al (2016) as between polyaromatic hydrocarbons (PAHs) and their partially hydrogenated forms (Raus & Hornekaer (2008); Menella et al 2012; Cazaux et al (2019)). Therefore, this mechanism can contribute to the formation of H 2 molecules on the surface of interstellar grains.…”
mentioning
confidence: 97%
“…The observations also show that the quasi-equilibrium is shifted towards HNCO because of a small barrier for the reaction H + HNCO → H 2 NCO. Similar dual-cycle mechanism might link also other unsaturated/saturated pairs of interstellar molecules; e.g., recent studies indicated the existence of similar cycles among CO, H 2 CO and CH 3 OH (Chuang et al (2016) as between polyaromatic hydrocarbons (PAHs) and their partially hydrogenated forms (Raus & Hornekaer (2008); Menella et al 2012; Cazaux et al (2019)). Therefore, this mechanism can contribute to the formation of H 2 molecules on the surface of interstellar grains.…”
mentioning
confidence: 97%
“…Each of these reactions increases the mass M by 1 Da. In a combined experimental and theoretical study we could show that C 24 H + 12 hydrogenation at T = 300 K is following a well-defined sequence of hydrogenation sites [10] that has later been confirmed by means of infrared spectroscopy [11]. The attachment barriers almost vanish for radicals with even numbers of attached H atoms and as a consequence, cations with odd s are observed at much higher intensities than cations with even s. Hydrogenation states with s = 5, 11 and 17 are particularly prominent due to their relatively high binding energies combined with a high barrier for the next hydrogenation to occur.…”
Section: [Cor + Sh]mentioning
confidence: 72%
“…For the smaller catacondensed PAHs anthracene and phenanthrene, the crossover occurs already between N = 2 and 4 additional H atoms (Diedhiou et al 2020). An infrared multi-photon dissociation study of super-hydrogenated coronene found the branching fractions to be comparable at N = 7 (Cazaux et al 2019). For coronene and the larger PAHs expected to be predominant in PDRs, it may be expected -though this has not been demonstrated -that hydrogenated species with the minimal amount of superhydrogenation to achieve catalytic H 2 formation could approach 100% stability against loss of native H atoms and backbone fragmentation.…”
Section: Implications For Astrophysicsmentioning
confidence: 99%
“…This was demonstrated in experiments where super-hydrogenated coronene (C 24 H 12+N , N = 1, 3, 5) cations were found to lose fewer of their native H atoms with increasing levels of super-hydrogenation following soft x-ray excitation at 285 eV (Reitsma et al 2014). More recent studies, however, showed that higher degrees of super-hydrogenation (N 6) led to increased carbon backbone fragmentation (Rapacioli et al 2018;Cazaux et al 2019). Taken together, these studies suggest the existence of a window of hydrogenation levels consistent with truly catalytic H 2 -formation without destruction of the native PAH.…”
Section: Introductionmentioning
confidence: 96%